THE CHARACTERS OF LOVE AND SHADOWS, BY ISABEL ALLENDE, IN CHILEAN DITACTORSHIP CONTEXT (TEL Tempo, Espaço e Linguagem, 2022)
This paper aims to analyze the dictatorship of book Of love and Shadow (1991), novel written by Isabel Allende. This opus, Of love and Shadow, is one of the most important and pioneering of Isabel’s career, in this, the topic of dictatorship is present at this moment, we consider some characters that suffer the consequences of military regime. The principal specialists of this paper about chilean dictatorship are Joan Garcés (1993) and Emir Sader (1984), who contributes so much with their books, Allende e as armas da política e Democracia e ditadura no Chile, to this study and we also emphasyze the importance of the book of Roberto Simon (2021), O Brasil contra a democracia: a ditadura, o golpe no Chile e a Guerra Fria na América do Sul, about this theme too. The another references were very important too as the books Trópicos do discurso (2001), by Hayden White, and O romance histórico brasileiro contemporâneo (1975-2000), by Antônio Roberto Esteves, and the article “Imagens do insólito e do maravilhoso: construções da historicidade na literatura hispano-americana”, by Ana Lúcia Trevisan . This analysis considers the period of time lived in the opus and how Gustavo Morante proceed in this political situation of their country, Chile, considering another characters around him. This study is a result of Master Thesis intitled “O casal de protagonistas em De amor e de sombra, de Isabel Allende: uma análise”.